Modulation of iron status biomarkers in tuberculosis-diabetes co-morbidity. (January 2018) - Kumar, Nathella Pavan; Banurekha, Vaithilingam V.; Nair, Dina; Dolla, Chandrakumar; Kumaran, Paul; Babu, Subash
Abstract: Tuberculosis (TB) and diabetes mellitus (DM) remain vital disease burdens in developing countries and the dual burden of DM and TB clearly signifies a growing global public health concern. While modulation of iron status biomarkers in TB is well described, very little is known about the association of these markers with TB-DM. To examine the association of circulating iron status biomarkers in TB disease, we examined the systemic levels of ferritin, hepcidin, soluble transferrin receptor (sTfR), transferrin, apotransferrin and hemopexin in pulmonary TB (PTB) individuals with DM (PTB-DM), without DM (PTB) and those with diabetes only (DM). Circulating levels of ferritin and hepcidin were significantly enhanced in PTB-DM and PTB compared to the DM group. On the other hand, the circulating levels of transferrin and apotransferrin were significantly diminished in PTB–DM and PTB compared to the DM group. The levels of ferritin and hepcidin exhibited a significant positive relationship with HbA1c, whereas apotransferrin exhibited negative relationship with HbA1c in PTB-DM and PTB. ROC analysis revealed that ferritin, hepcidin and transferrin are markers that can distinguish PTB-DM from DM individuals. Our results suggest that some of these circulating iron status markers could prove useful as biomarkers to monitor disease severity.